Trends in skin cancer incidence in Songkhla, Southern Thailand, 1989–2020: A population-based study on the impact of geographic variation - Suchaya Pajareeyaphan; Paramee Thongsuksai; Hutcha Sriplung; Wit Wichaidit (PLoS ONE, 2026)
Background The incidence trends of skin cancer are increasing across the world. However, data from Southeast Asian countries, including Thailand, are limited. Songkhla, a province in southern Thailand, has a predominant occupation and religion across different geographic areas which may influencing the incidence. This study aimed to assess the trends in skin cancer incidence in Songkhla according to age, calendar period, birth cohort, and geographical areas. Methods The study included patients diagnosed with squamous cell carcinoma, basal cell carcinoma, and melanoma of the skin between 1989 and 2020, as recorded in the Songkhla population-based cancer registry. Geographic areas were classified into four categories with remaining groups: urban VS rural, Muslim VS Buddhist, fishing and farming VS other occupations, and rubber plantation VS other occupations. Age-standardized incidence rates (per 100,000 population) were calculated, and trend analyses were performed using Joinpoint regression and age-period-cohort analysis. Results The incidence of skin cancer in men declined after 2001 with annual percentage change rates of –2.24%, while it remained stable among women. However, when stratified by geographic area, the incidence among women showed a decline after 2016 in some areas. Overall, incidence rates were higher in urban than in rural areas, lower in predominantly Muslim than Buddhist areas, and lower in rubber plantation areas compared with other occupational areas. Age was positively associated with skin cancer incidence. The cohort effect demonstrated a decreasing rate ratio (RR) among men born after 1945, while no significant change in RR was observed among women. The period effect showed no significant influence on RR in either sex. Conclusions Although the incidence of skin cancer in Songkhla, Thailand, has shown a decreasing trend in men and remained stable in women, awareness and prevention should continue to be emphasized, particularly among older individuals who are more prone to UV radiation exposure.